The human defence. - EDMONDS, DAVID (Prospect, 2018)
The article discusses how computers have changed the sport of chess. Topics discussed include ways in which Deep Blue and other chess computers have helped human players, the application of machine learning in computer chess, and the World Chess Championship which will feature current world chess champion Magnus Carlsen and Italian-American player Fabiano Caruana.